Analisis Retorika Dakwah Ustadz Hanan Attaki dalam Video Youtube “Kalo lagi Mentok, Harus Gimana?”: Kajian Retorika Aristoteles - Hindun; Falasifa; Hanna Maulida Syifa; Mita Mar'atul Fauziah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the application of Aristotle's rhetorical principles in the preaching video of ustadz Hanan Attaki entitled “Kalo Lagi Mentok, Harus Gimana?” The background of this research is the importance of understanding the stages of rhetoric in preaching to enhance understanding of the influence and effectiveness of the message conveyed. The aim of this research is to explain the stages of rhetoric in ustadz Hanan Attaki's preaching video based on Aristotle's theory. The method used is descriptive qualitative, with data collection through video research, transcription, and content analysis. The results of the study show that ustadz Hanan Attaki successfully applies Aristotle's five stages of rhetoric (Inventio, Dispositio, Elocutio, Memoria, and Pronuntiatio) effectively in his preaching. The benefit of this research is an increased understanding of rhetoric in the context of Islamic preaching and the relevance and effectiveness of its use in delivering religious messages to modern audiences.